Battery Stack

By using terminals with a high melting point, the battery stack prevents chemical reactions with sulfur, addressing the issue of increased internal resistance and maintaining performance.

JP7613400B2Active Publication Date: 2025-01-15TOYOTA JIDOSHA KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022042849
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-03-17
Publication Date
2025-01-15
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

The increase in internal resistance in battery stacks containing sulfur-containing components is a challenge that existing technologies have not adequately addressed.

Method used

The battery stack is configured with negative and positive electrode terminals made of metals with a melting point between 260°C to 300°C, which are sintered or fused bodies, ensuring they do not melt during typical bonding processes, thereby reducing chemical reactions with sulfur and maintaining low internal resistance.

Benefits of technology

This configuration effectively suppresses the increase in internal resistance by preventing chemical reactions between sulfur and the terminals during manufacturing, ensuring the battery stack maintains optimal performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007613400000001
    Figure 0007613400000001
  • Figure 0007613400000002
    Figure 0007613400000002
Patent Text Reader

Abstract

To provide a battery laminate that can suppress an increase in internal resistance.SOLUTION: A battery laminate is obtained by one or more power generation elements in which a negative electrode layer, a solid electrolyte layer, and a positive electrode layer are stacked in this order, and includes: a negative electrode terminal disposed on a side surface of the power generation element and electrically connected to the negative electrode layer; and a positive electrode terminal disposed on the side surface of the power generation element and electrically connected to the positive electrode layer. The power generation element contains sulfur, and the negative terminal and the positive terminal are sintered or fused metal bodies having a melting point in a range of 260°C to 300°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a battery stack. [Background technology]

[0002] Patent Document 1 discloses a solid-state battery including a solid-state battery main body formed by alternately stacking positive and negative electrode layers with a solid electrolyte layer interposed therebetween; end surface electrodes electrically connected to each of the positive and negative electrode layers and disposed on each of two side surfaces of the solid-state battery main body; and a bottom surface electrode electrically connected to the end surface electrodes and disposed on the bottom surface side of the solid-state battery main body. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2021 / 132504 Summary of the Invention [Problem to be solved by the invention]

[0004] The present inventors have investigated suppressing an increase in the internal resistance of a battery stack having a specified structure, the battery stack having a power generating element that contains a component containing sulfur, such as a sulfide solid electrolyte and / or a sulfur-based active material.

[0005] An object of the present disclosure is to provide a battery stack that can suppress an increase in internal resistance. [Means for solving the problem]

[0006] The present inventors have found that the above object can be achieved by the following means: Aspect 1 one or more power generating elements each having a negative electrode layer, a solid electrolyte layer, and a positive electrode layer stacked in this order; a negative electrode terminal disposed on a side surface of the power generating element and electrically connected to the negative electrode layer; and a positive electrode terminal disposed on a side surface of the power generating element and electrically connected to the positive electrode layer; The power generating element contains sulfur, The negative electrode terminal and the positive electrode terminal are sintered bodies or fused bodies of metals having a melting point in the range of 260°C to 300°C. Battery stack. Aspect 2 The negative electrode layer has a structure in which a negative electrode current collector layer and a negative electrode active material layer are laminated on each other, and the negative electrode terminal is electrically connected to the negative electrode current collector layer, and the positive electrode layer has a structure in which a positive electrode current collector layer and a positive electrode active material layer are laminated on each other, and the positive electrode terminal is electrically connected to the positive electrode current collector layer. 2. The battery stack of embodiment 1. Aspect 3 3. The battery stack of claim 1 or 2, wherein the metal is a Sn alloy. Aspect 4 4. The battery stack of claim 3, wherein the Sn alloy is an alloy of Sn with Au or Ni. Aspect 5 The battery stack according to any one of aspects 1 to 4, wherein a power generating element is sealed by an exterior body, the negative electrode terminal, and the positive electrode terminal. Aspect 6 6. The battery stack according to any one of Aspects 1 to 5, wherein the sulfur is contained in a sulfide solid electrolyte and / or a sulfur-based active material. Aspect 7 The battery stack of any one of aspects 1 to 6, wherein the negative electrode terminal and the positive electrode terminal extend to a portion of at least one end face of the battery stack in the stacking direction. Aspect 8 The battery stack according to any one of aspects 1 to 7, which is a lithium ion secondary battery. Effect of the Invention

[0007] According to the present disclosure, it is possible to provide a battery stack that can suppress an increase in internal resistance. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram of a battery stack 100 according to a first embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram of a battery stack 200 according to a second embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0010] The battery stack of the present disclosure is a battery stack comprising one or more power generating elements each having a negative electrode layer, a solid electrolyte layer, and a positive electrode layer stacked in this order, a negative electrode terminal disposed on a side surface of the power generating element and electrically connected to the negative electrode layer, and a positive electrode terminal disposed on a side surface of the power generating element and electrically connected to the positive electrode layer, the power generating element contains sulfur, and the negative electrode terminal and the positive electrode terminal are sintered bodies or fused bodies of a metal having a melting point in the range of 260°C to 300°C.

[0011] The battery stack may be configured such that one or more power generating elements, each having a negative electrode layer, a solid electrolyte layer, and a positive electrode layer stacked in this order, are stacked together, with a negative electrode terminal electrically connected to the negative electrode layer and disposed on a side of the power generating element, and a positive electrode terminal electrically connected to the positive electrode layer and disposed on a side of the power generating element.

[0012] It is conceivable that a battery stack having such a configuration would be used by being fixed to a base material, such as a printed circuit board, by soldering or the like.

[0013] However, sulfur-containing components that can be used in the power generating element, such as a sulfide solid electrolyte and / or a sulfur-based active material, may chemically react with water, and therefore, when the power generating element contains sulfur, the battery stack is required to have sufficient sealing properties.

[0014] From the viewpoint of providing a sufficient sealing property to the battery stack, it is considered that the external terminals, i.e., the negative and positive terminals, are formed by sintering or fusion bonding.

[0015] However, when sulfur is heated to high temperatures, it may chemically react with other components of the power generating element, external terminals, etc.

[0016] Therefore, if the sintering temperature or melting temperature of the metal used in the external terminals is high, when the external terminals are formed by sintering or melt bonding during the manufacture of the battery stack, a chemical reaction may occur between the sulfur contained in the power generating element and the metal forming the external terminals, and / or between the sulfur in the power generating element and other components, resulting in a decrease in the internal resistance of the manufactured battery stack.

[0017] In this regard, in the battery stack of the present disclosure, the external terminals are sintered or fused bodies of a metal having a melting point in the range of 260°C to 300°C. Such metals have melting points of 260°C or higher, which is higher than the general heating temperature in the solder reflow process used to join the battery stack to a printed circuit board or the like. This makes it possible to prevent the external terminals from melting when joining the battery stack to a printed circuit board or the like. Melting of the external terminals may cause problems such as a decrease in the hermeticity of the battery stack in some cases.

[0018] In addition, because such metals have melting points of 300°C or lower, they can be melted to form external terminals at temperatures lower than the reaction temperature of sulfur that may be used in the power generating element, which makes it possible to suppress an increase in the internal resistance of the battery stack caused by a reaction of sulfur in the power generating element during the manufacture of the battery stack.

[0019] The battery stack of the present disclosure can have a configuration as shown in FIG. 1, for example.

[0020] Fig. 1 is a schematic diagram of a battery stack 100 according to a first embodiment of the present disclosure. More specifically, Fig. 1 is a cross-sectional view in the stacking direction of the battery stack 100 according to the first embodiment of the present disclosure.

[0021] 1, a battery stack 100 according to the first embodiment of the present disclosure includes a plurality of power generating elements 110, each of which has a negative electrode layer 111, a solid electrolyte layer 112, and a positive electrode layer 113 stacked in this order, and includes a negative electrode terminal 141 electrically connected to the negative electrode layer 111 and disposed on a side of the power generating element 110, and a positive electrode terminal 142 electrically connected to the positive electrode layer 113 and disposed on a side of the power generating element 110. In addition, an exterior body 130 is disposed on both sides of the battery stack 100 in the stacking direction and on a side (not shown) on which no external terminals are disposed, whereby the power generating element 110 is sealed by the exterior body 130, the negative electrode terminal 141, and the positive electrode layer 113.

[0022] In addition, an insulating electrode end layer 120 is arranged between the negative electrode active material layer and the outer casing 130 and between the solid electrolyte layers of adjacent power generating elements 110, thereby suppressing electrical contact between the negative electrode layer 111 and the outer casing 130, between the negative electrode layer 111 and the positive electrode terminal 142, and / or between the positive electrode layer 113 and the negative electrode terminal 141.

[0023] Here, the power generating element 110 contains sulfur, and the negative electrode terminal 141 and the positive electrode terminal 142 are sintered bodies or fused bodies of metal having a melting point in the range of 260°C to 300°C.

[0024] 2, in a battery stack 200 according to the second embodiment of the present disclosure, the negative electrode layer 211 has a structure in which a negative electrode current collector layer 211a and a negative electrode active material layer 211b are stacked on each other, and the negative electrode terminal 241 can be electrically connected to the negative electrode current collector layer 211a. Similarly, the positive electrode layer 213 has a structure in which a positive electrode current collector layer 213a and a positive electrode active material layer 213b are stacked on each other, and the positive electrode terminal 242 can be electrically connected to the positive electrode current collector layer 213a.

[0025] The battery stack of the present disclosure may be a lithium ion secondary battery.

[0026] 《Power Generation Element》 In the present disclosure, the power generating element is formed by laminating an anode layer, a solid electrolyte layer, and a cathode layer in this order.

[0027] The battery stack has a structure in which one or more power generating elements are stacked, particularly a structure in which multiple power generating elements are stacked in a monopolar structure. When the battery stack has only one power generating element, the battery stack has the configuration of a single cell. When the battery stack has a structure in which multiple power generating elements are stacked, the stacking direction of each power generating element in the battery stack is the same as the stacking direction of the negative electrode layer, solid electrolyte layer, and positive electrode layer in the power generating element.

[0028] The power generating element contains sulfur. Here, the sulfur may be contained in, for example, a sulfide solid electrolyte and / or a sulfur-based active material. The sulfur may be contained in any of the negative electrode layer, the solid electrolyte layer, and the positive electrode layer.

[0029] The sulfide solid electrolyte may be, for example, a sulfide-based amorphous solid electrolyte, a sulfide-based crystalline solid electrolyte, or an argyrodite-type solid electrolyte. More specifically, the sulfide solid electrolyte may be a Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.

[0030] The sulfur-based active material is an active material containing at least S element. The sulfur-based active material may or may not contain Li element. Examples of the sulfur-based active material include elemental sulfur, lithium sulfide (Li2S), and lithium polysulfide (Li2S x , 2≦x≦8).

[0031] <Negative electrode layer> The negative electrode layer may have a structure in which, for example, a negative electrode current collector layer and a negative electrode active material layer are laminated on each other, and in this case, the negative electrode terminal may be electrically connected to the negative electrode current collector layer. Note that the negative electrode layer may not have a negative electrode current collector layer, and in this case, the negative electrode terminal may be electrically connected to the negative electrode active material layer by directly contacting the negative electrode current collector layer.

[0032] (Negative electrode active material layer) The negative electrode active material layer contains a negative electrode active material and, optionally, a solid electrolyte. In addition, the negative electrode active material layer may contain additives used in the negative electrode active material layer of a lithium ion battery, such as a conductive assistant or a binder, depending on the intended use or purpose.

[0033] The negative electrode active material may be, for example, a material capable of absorbing and releasing metal ions such as lithium ions. Examples of the material capable of absorbing and releasing metal ions such as lithium ions include, but are not limited to, an alloy-based negative electrode active material or a carbon material.

[0034] The alloy-based negative electrode active material is not particularly limited, and examples thereof include Si alloy-based negative electrode active materials and Sn alloy-based negative electrode active materials. The Si alloy-based negative electrode active material includes silicon, silicon oxide, silicon carbide, silicon nitride, and solid solutions thereof. The Si alloy-based negative electrode active material can include elements other than silicon, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, Ti, and the like. The Sn alloy-based negative electrode active material can include tin, tin oxide, tin nitride, and solid solutions thereof. The Sn alloy-based negative electrode active material can include elements other than tin, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Ti, Si, and the like. Among these, the Si alloy-based negative electrode active material is preferred.

[0035] The carbon material is not particularly limited, and examples thereof include hard carbon, soft carbon, graphite, and the like.

[0036] The solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for an all-solid-state battery can be used. More specifically, examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer electrolytes.

[0037] Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl xetc.; or combinations thereof, but are not limited to these.

[0038] An example of an oxide solid electrolyte is Li7La3Zr2O 12、 Li 7-x La3Zr 1-x Nb x O 12、 Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x (LiPON), but is not limited to these.

[0039] The sulfide solid electrolyte, the oxide solid electrolyte, and the nitride solid electrolyte may be glass, glass ceramics, or a crystalline material. Glass can be obtained by amorphous processing of a raw material composition (e.g., a mixture of Li2S and P2S5). Examples of amorphous processing include mechanical milling. The mechanical milling may be dry mechanical milling or wet mechanical milling, with the latter being preferred. This is because the raw material composition can be prevented from adhering to the wall surface of a container or the like. Glass ceramics can be obtained by heat treating glass. Crystalline materials can be obtained, for example, by performing a solid-phase reaction process on the raw material composition.

[0040] Examples of the polymer electrolyte include, but are not limited to, polyethylene oxide (PEO) and polypropylene oxide (PPO).

[0041] The binder may be, for example, but is not limited to, materials such as polyvinylidene fluoride (PVdF), carboxymethyl cellulose (CMC), butadiene rubber (BR) or styrene butadiene rubber (SBR), or combinations thereof.

[0042] The conductive assistant may be a known one, for example, a carbon material, metal particles, etc. The carbon material may be at least one selected from the group consisting of carbon black such as acetylene black or furnace black, vapor grown carbon fiber (VGCF), carbon nanotubes, and carbon nanofibers, and from the viewpoint of electronic conductivity, may be at least one selected from the group consisting of VGCF, carbon nanotubes, and carbon nanofibers. The metal particles may be nickel, copper, iron, stainless steel, etc.

[0043] (Negative electrode current collector layer) The material used for the negative electrode current collector layer may be, but is not limited to, stainless steel (SUS), aluminum, copper, nickel, iron, titanium, carbon, etc. Among these, the material for the negative electrode current collector layer is preferably copper.

[0044] The shape of the negative electrode current collector layer is not particularly limited, and examples thereof include a foil-shaped, plate-shaped, or mesh-shaped electronically conductive material, and a layer-shaped material formed from an electronically conductive material powder and a binder. Among these, a foil-shaped electronically conductive material is preferred.

[0045] <Solid electrolyte layer> The solid electrolyte layer can contain a solid electrolyte and optionally a binder.

[0046] As the solid electrolyte and the binder, those described above in relation to the "(negative electrode active material layer)" can be appropriately used.

[0047] <Positive electrode layer> The positive electrode layer may have a structure in which a positive electrode current collector layer and a positive electrode active material layer are laminated on each other, and in this case, the positive electrode terminal may be electrically connected to the positive electrode current collector layer. Note that the positive electrode layer may not have a positive electrode current collector layer, and in this case, the positive electrode terminal may be electrically connected to the positive electrode active material layer by directly contacting the positive electrode current collector layer.

[0048] (Cathode active material layer) The positive electrode active material layer contains a positive electrode active material and, optionally, a solid electrolyte. In addition, the positive electrode active material layer may contain additives used in the positive electrode active material layer of a lithium ion battery, such as a conductive assistant or a binder, depending on the intended use or purpose.

[0049] The positive electrode active material is, for example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y M y The material may be, but is not limited to, a Li-Mn spinel substituted with a different element having a composition represented by O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn).

[0050] In addition, such a positive electrode active material may be, for example, a sulfur-based active material. Here, the sulfur-based active material is an active material containing at least S element. The sulfur-based active material may or may not contain Li element. Examples of the sulfur-based active material include elemental sulfur, lithium sulfide (Li2S), and lithium polysulfide (Li2S x , 2≦x≦8).

[0051] As the solid electrolyte, the conductive assistant, and the binder, those described above in relation to the "(negative electrode active material layer)" can be appropriately used.

[0052] (Positive electrode current collector layer) The material used for the positive electrode current collector layer may be, but is not limited to, stainless steel (SUS), aluminum, copper, nickel, iron, titanium, carbon, etc. Among these, the material for the positive electrode current collector layer is preferably aluminum.

[0053] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil-shaped, plate-shaped, or mesh-shaped electronically conductive material, etc. Examples of the material include a layer-shaped material formed from an electronically conductive material powder and a binder. Among these, a foil-shaped electronically conductive material is preferred.

[0054] Negative and positive terminals The battery stack of the present disclosure has a negative electrode terminal that is electrically connected to the negative electrode layer and is disposed on a side surface of the power generating element, and a positive electrode terminal that is electrically connected to the positive electrode layer and is disposed on a side surface of the power generating element.

[0055] The negative electrode terminal and the positive electrode terminal are made of a sintered body or a fused body of a metal having a melting point in the range of 260°C to 300°C.

[0056] The metal usable for the negative electrode terminal and the positive electrode terminal can be any metal or metal alloy having a melting point in the range of 260° C. to 300° C. Examples of such metals include Pb and Sn alloys. Examples of Sn alloys include alloys of Sn and Au or Ni.

[0057] The melting point of metals that can be used for the negative and positive electrode terminals may be 260°C or more, 265°C or more, 270°C or more, or 275°C or more, and may be 300°C or less, 295°C or less, 290°C or less, 285°C or less, or 280°C or less.

[0058] The negative and positive terminals can extend to a portion of at least one end face of the battery stack in the stacking direction. When the battery stack has such a configuration, the end faces to which the negative and positive terminals extend can be fixed to the printed circuit board by, for example, soldering, thereby electrically connecting the battery stack to a circuit on the printed circuit board.

[0059] More specifically, as shown in FIG. 1, the negative electrode terminal 141 and the positive electrode terminal 142 can extend to a portion of the end faces of the battery stack 100 in the stacking direction (the upper and lower sides of the battery stack 100 in FIG. 1).

[0060] Exterior Body In the battery stack of the present disclosure, the power generating element is preferably sealed by the exterior body, the negative electrode terminal, and the positive electrode terminal.

[0061] Here, the exterior body may be made of any material capable of sealing the power generating element, such as a resin or ceramics. [Explanation of symbols]

[0062] 100 and 200 Battery Stacks 110 and 210 Power generation elements 111 and 211 negative electrode layers 112 and 212 solid electrolyte layers 113 and 213 positive electrode layers 120 and 220 electrode end layers 130 and 230 Exterior body 141 and 241 Negative terminal 142 and 242 Positive terminal 211a Negative electrode current collector layer 211b Negative electrode active material layer 213a Positive electrode current collector layer 213b Cathode active material layer

Claims

1. one or more power generating elements each having a negative electrode layer, a solid electrolyte layer, and a positive electrode layer stacked in this order; a negative electrode terminal disposed on a side surface of the power generating element and electrically connected to the negative electrode layer; and a positive electrode terminal disposed on a side surface of the power generating element and electrically connected to the positive electrode layer; The power generating element contains sulfur, The negative electrode terminal and the positive electrode terminal are sintered bodies or fused bodies of metals having a melting point in the range of 260°C to 300°C, the negative electrode layer has a negative electrode active material layer and does not have a negative electrode current collector layer, the negative electrode terminal is in direct contact with the negative electrode active material layer and is thereby electrically connected to the negative electrode layer, the positive electrode layer has a positive electrode active material layer and does not have a positive electrode current collector layer, and the positive electrode terminal is in direct contact with the positive electrode active material layer and is thereby electrically connected to the positive electrode layer; Battery stack.

2. The battery stack of claim 1 , wherein the metal is a Sn alloy.

3. The battery stack according to claim 2 , wherein the Sn alloy is an alloy of Sn and Au or Ni.

4. 4. The battery stack according to claim 1, wherein a power generating element is sealed by an exterior body, the negative electrode terminal, and the positive electrode terminal.

5. The battery stack according to any one of claims 1 to 4, wherein the sulfur is contained in a sulfide solid electrolyte and / or a sulfur-based active material.

6. 6. The battery stack according to claim 1, wherein the negative electrode terminal and the positive electrode terminal extend to a portion of at least one end face in a stacking direction of the battery stack.

7. The battery stack according to any one of claims 1 to 6, which is a lithium ion secondary battery.

Citation Information

Patent Citations

  • All-solid lithium ion secondary battery and its manufacturing method

    JP2008251225A

  • All-solid-state lithium ion secondary battery and package

    WO2018181288A1

  • Secondary cell

    WO2018186449A1

  • Battery

    WO2021009959A1

  • Solid-state battery

    WO2021132504A1